Studi Kasus Familly Helath Education Dengan Media Lembar Balik (Flip Chart) untuk Meningkatkan Pengetahuan dan Sikap Keluarga Dalam pencegahan Penularan TB Paru - Karunia, Ajeng Tri; Reliani, Reliani; Husna, Anis rosyiatul; Yumni, Fathiya Lutfil (Universitas Muhammadiyah Surabaya, 2024)
Background: Pulmonary TB is a dangerous infectious disease which is one of the causes of death. One way of transmitting pulmonary TB is through sputum splashes (droplets). good knowledge and attitudes to be able to prevent transmission of tuberculosis (TB). To increase knowledge and attitudes it is necessary to provide education using media, namely flip chart media. Objective: to identify knowledge and attitudes before and after being given family health education using flip chart media in preventing tuberculosis (TB) transmission. Methods: This research is a descriptive study that describes or describes the events that occurred during the research, the design used by the researcher is a case study, the sampling technique is purposive sampling, the number of samples used by the researcher is 10 family respondents with tuberculosis (TB) patients and data collection uses knowledge and attitude questionnaire. Results and Discussion: This research was obtained before being given education there was less knowledge (30%) and sufficient (20%), the level of previous attitudes, negative attitudes (20%), while the level of knowledge and attitudes after being given education obtained the results of the level of knowledge enough (30%) and good (70%), and there is an increase in attitude to (100%) all respondents are positive. And the conclusion of this study is that there is an increase in the level of knowledge and attitudes before and after being given family health education with flip chart media in preventing TB transmission, and this media is very effective in implementing TB health education promotion